OPTIMALISASI PENDIDIKAN AGAMA ISLAM MELALUI EKSTRAKURIKULER AL BANJARI DI SMA WACHID HASYIM 2 TAMAN SIDOARJO - Suryansyah Hidayat, Mochammad; Yusron Maulana El-Yunusi, Muhammad (ILJ: Islamic Learning Journal, 2024)
This research aims to optimize Islamic religious education through extracurricular activities Al Banjari at Wachid Hasyim 2 Taman High School in Taman Sidoarjo. The method used is quantitative involving 5 informants, namely 1 school principal, 1 vice principal, 1 Al Banjari teacher, and 2 students. The approach used is descriptive with a phenomenological approach. The Al Banjari extracurricular at Wachid Hasyim 2 Taman High School in Taman Sidoarjo is the focus of the research due to its significant potential in strengthening Islamic religious education within the school environment. Al Banjari activities serve not only as a platform for religious learning but also enrich Islamic culture and traditions. By understanding the experiences and perceptions of the informants, this research aims to identify factors influencing the effectiveness of Al Banjari extracurricular activities in optimizing Islamic religious education at Wachid Hasyim 2 High School in Taman Sidoarjo. The results of this research are expected to provide a comprehensive overview of the contribution of Al Banjari in enhancing the understanding of Islam among students. Thus, potential and challenges in implementing Al Banjari activities can be identified, along with providing recommendations for further development. This research makes an important contribution to strengthening Islamic religious education in schools through extracurricular approaches. With a better understanding of the factors influencing the effectiveness of Al Banjari extracurricular activities, it is hoped that improvements and better developments can be made to enhance the quality of Islamic religious education at Wachid Hasyim 2 High School in Taman Sidoarjo.